Understanding Allergy through the Holistic Principles of Homoeopathy (Homoeopathy for All, 2026)
The term “Allergy” was coined by  an Austrian paediatrician named  Clemens von Pirquet in 1906 and  has its roots derived from two  Greek words namely allos ("other"  or "different") and ergon ("activity"  or "reaction"). It is described as an  exaggerated response of the immune  system to foreign substances that get  inside the body. These foreign bodies  are usually harmless substances such  as pollens, food, dust, insects, ticks,  moulds and drugs which are termed  as Allergens.
Keywords: Allergic disease; hypersensitivity reactions; EPIDEMIOLOGY; prevalence of allergy